2020
DOI: 10.1177/1055665620936442
|View full text |Cite
|
Sign up to set email alerts
|

Family Impact of Child Oro-Facial Cleft

Abstract: Objective: To describe the association between children’s orofacial cleft (OFC) and families’ quality of life (QoL), using the short-form Family Impact Scale questionnaire (FIS-SF). Also assessed were the psychometric properties of the FIS-SF, as well as whether certain demographic and clinical variables impacted the family. Design: Observational cross-sectional study. Setting: Tertiary care public children’s hospital in New South Wales, Australia. Participants: Parents/caregivers of children with OFC. Main ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Meanwhile, QOL should not be limited to the patient as circumstance of the disease influences the QOL of the whole family. In addition, there are some instruments pay attention to the QOL of family members ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, QOL should not be limited to the patient as circumstance of the disease influences the QOL of the whole family. In addition, there are some instruments pay attention to the QOL of family members ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The family’s perspective should also be assessed because chronic illness, such as cleft lip and palate, inevitably impacts the day-to-day functioning since health care interventions will lead to family needs and concerns [ 30 ]. Family activities, parental emotions and family conflict were identified as significant factors negatively affecting parents OHRQoL in this total sample.…”
Section: Discussionmentioning
confidence: 99%
“…Family activities, parental emotions and family conflict were identified as significant factors negatively affecting parents OHRQoL in this total sample. Previous studies pointed out some factors that may explain the impact on quality of life of caregivers, namely repeated consultations, financial implications, parental time off work, less time for other family members, stigmatization and peer victimization of their child and the impact of orthodontic appliances in speech, mastication and social interaction of the child [ 30 , 31 ]. On the other hand, the family finances domain did not show a significant difference between the two groups ( p = 0.051).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] The concept of child health includes both the child and the family because of children's dependence on their caregivers and family. 6 Studies have shown that the sociodemographic characteristics and the health status of mothers are associated with parent-child interactions, which as a result may influence the children's health outcomes. 7 Hence, the psychological adjustment of parents of children with CL/P is an important research subject.…”
Section: Introductionmentioning
confidence: 99%